Dendrochronological dating of two violins from private collections in Slovenia - Čufar, Katarina (Zbornik gozdarstva in lesarstva, 2010)
Dendrochronological analyses were made in two violins from private collectionsin Slovenia with an aim to date the wood of their resonance boards,to assess the time of their fabrication, to define the provenance of the wood, and to establish whether the labels of the instruments were original. The origin, the history and the exact age of the instruments had previously not been known. Tree-ring measurements were done on the surface of the bellies. In violin 1, it was made of one radial board, in violin 2 of two radial boards of Norway spruce (Picea abies). In violin 1, we measured 248 tree-rings and the year of the youngest ring was 1808. The dating was confirmed with more than 20 tree-ring chronologies from Austria, Germany, and Italy. The maximal value of the cross-dating parameter t-value after Hollstein(TH) was 12.4. In violin 2, we measured 141 and 137 tree-rings on each side of the belly, and the year of the youngest ring was 1640. The dating was also obtained by cross-dating with over 20 chronologies and confirmed with statistically significant TH up to 9.2. The year of the last ring in both cases corresponded with the terminus post quem, which indicated that the belly (instrument) was fabricated after the year of formation of the youngest ring. There is no evidence about the duration of seasoning and storage of the lumber, or how many tree-rings were removed when the instrumentwas manufactured. Our dendro-provenance study showed that the violin 1 most likely originated from Austria or southern Germany. The wood for the belly of the violin 2 possibly originated from Austria and the sequence significantly matched a chronology built from the instruments made by Jacob Stainer. In both instruments, the dendrochronological dating did not confirm the inscriptions on the labels on the inside of the instrument. The presented investigation was performed in 2008 and 2009 and is to our knowledge the first dendrochronological dating of music instruments in Slovenia.
Keywords: branike; dendrokronologija; les; Picea abies; smreka; violine